2019
DOI: 10.1155/2019/3241263
|View full text |Cite
|
Sign up to set email alerts
|

Bone Formation and Adaptive Morphology of the Anterior Tibial Muscle in 3-mm Daily Lengthening Using High-Fractional Automated Distraction and Osteosynthesis with the Ilizarov Apparatus Combined with Intramedullary Hydroxyapatite-Coated Wire

Abstract: Purpose. We studied osteogenesis and morphofunctional features of the anterior tibial muscle using 3-mm high-frequency automated lengthening with the Ilizarov apparatus alone and in combination with intramedullary nailing. Material and Methods. Tibia was lengthened with a round-the-clock automated distractor at a 3-mm daily rate for 10 days in 16 mongrel dogs. In group 1 (n = 8), a 1.8-mm intramedullary titanium wire coated with hydroxyapatite was introduced into the tibial canal followed by Ilizarov frame mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The process of distraction histogenesis can recreate a vascular network, which enhances the wound repair process. 17,18 Notably, the ulcer in the middle of the tibia was atypical in this patient. The precise execution of periosteal distraction and bone transport in this specific region poses a significant risk of postoperative subperiosteal or bone marrow infection.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The process of distraction histogenesis can recreate a vascular network, which enhances the wound repair process. 17,18 Notably, the ulcer in the middle of the tibia was atypical in this patient. The precise execution of periosteal distraction and bone transport in this specific region poses a significant risk of postoperative subperiosteal or bone marrow infection.…”
Section: Discussionmentioning
confidence: 66%
“…The process of distraction histogenesis can recreate a vascular network, which enhances the wound repair process. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…It was stated that teriparatide treatment during the consolidation phase of distraction osteogenesis doubled the mineralization rate of the regenerate when compared to no treatment. The experiment on a canine model attempted automated high-frequency distraction with a daily 3-mm rate and confirmed that the bone had the potential for regeneration under the conditions described but there were concerns about the response of soft tissues and joints[ 78 ]. Histological differences were observed in bone and muscle tissue when Ilizarov fixation was supplemented by intramedullary HA-coated thin nails compared with no intramedullary stabilization in that experiment.…”
Section: Current Clinical Practice and Research In The Ilizarov Techniques Of Bone Reconstructionmentioning
confidence: 99%
“…The importance of intraosseous and periosteal blood supply for the formation of bone regenerate has been proven by experimental studies 1–8 . With intramedullary reinforcement of the regenerate with wires, a positive effect on its tissue regeneration was noted 9,10 . When using an intramedullary nail, it is impossible to avoid disruption of the intraosseous blood supply 5 .…”
Section: Introductionmentioning
confidence: 99%